2018
DOI: 10.1093/cid/cix1086
|View full text |Cite
|
Sign up to set email alerts
|

Daily and Nondaily Oral Preexposure Prophylaxis in Men and Transgender Women Who Have Sex With Men: The Human Immunodeficiency Virus Prevention Trials Network 067/ADAPT Study

Abstract: NCT01327651.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 19 publications
2
64
0
Order By: Relevance
“…Event-driven PrEP use may lead to lower adherence compared to daily use, as suggested by other studies [13,24]. In our study, we found a proportion of covered sex days of 67% while on event-driven and 96% while on daily PrEP.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Event-driven PrEP use may lead to lower adherence compared to daily use, as suggested by other studies [13,24]. In our study, we found a proportion of covered sex days of 67% while on event-driven and 96% while on daily PrEP.…”
Section: Discussionsupporting
confidence: 76%
“…In our study, we found a proportion of covered sex days of 67% while on event‐driven and 96% while on daily PrEP. In the Adapt study, the proportion covered sex acts was 74% and 85% among MSM in Bangkok and 52% and 75% among women in Capetown, for event‐driven and daily PrEP respectively . It should be noted however that participants of the Adapt study were randomly assigned to a PrEP regimen, as opposed to our study, where participants self‐selected and could switch between daily and event‐driven, according their preference, during the entire follow‐up period.…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, we did not find this association for on‐demand/intermittent users, indicating that daily PrEP use without health insurance coverage is likely too expensive for some, and the high cost prevents access to all people who could benefit from it. This is noticeable in light of recent results indicating that in some populations daily PrEP might allow for more intercourse events to be protected against HIV . In contrast, about half of the informal PrEP users indicated that generic PrEP would be affordable to them.…”
Section: Discussionmentioning
confidence: 91%
“…Setting programmatic benchmarks for adherence is essential for identifying shortfalls for further evaluation and intervention. Daily adherence will be the goal for most individuals , but perfection need not be a barrier to potential users ; event‐driven and seasonal use of PrEP present additional challenges for assessing adherence that require consideration. Given programmatic constraints, adherence should be measured through the most reasonably accessible and preferably objective measure .…”
Section: Discussionmentioning
confidence: 99%